PERAN DIGITALISASI PENDIDIKAN TERHADAP PROSES PEMBELAJARAN SISWA DI MASA PANDEMI COVID-19 - Anna Sardiana; Aditama Setyo Moekti (DEVOSI, 2022)
Education is the third pillar after health and economics, so traditional education must be able to answer the latest challenges by changing learning models, both elementary, junior high, high school, and university students. So far, education is still using traditional face-to-face methods, and distance learning (PJJ) is being implemented. Distance learning (PJJ) is applied based on the current situation and conditions, in accordance with the recommendation of the Government of the Republic of Indonesia that carrying out activities of working from home, learning from home, and worship from home. These things underlie the change in the learning process from traditional methods to modern methods or what is called the Digitalization of Education. The purpose of digitizing education is to make it easier for students to learning from home and teachers to teach from home and the knowledge gained remains effective, so that it is also in accordance with the recommendation of the Government of the Republic of Indonesia.